2017
DOI: 10.5482/hamo-16-07-0019
|View full text |Cite
|
Sign up to set email alerts
|

Management of chronic hepatitis C in 2017

Abstract: Hepatitis C virus (HCV) represents one of the most common aetiologies of chronic liver disease and causes a major global health burden. Globally an estimated 80 million people are chronically infected, but the majority of whom is still undiagnosed. Prior to the discovery of the virus in 1989 a significant number of patients were exposed and consecutively infected with HCV via contaminated transfusions, as it is a blood-borne disease. Chronic HCV infection pursues a progressive course that ultimately results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
3
1
Order By: Relevance
“…Our findings correlate with the recent phase 3 trials done, which showed that DAA therapy achieved Daclatasvir-Sofosbuvir Combination Therapy Pak Armed Forces Med J 2023; 73(5): 1520 high SVR rates (more than 90% for genotype-1, 80-90% for genotype-2, 60-70% for genotype-3) for compensated cirrhotic patients, with high tolerance & relatively low rates of adverse effects. 15 In our study, genotype 3(81.3%) was more common, followed by genotype 1(11.8%), with few cases of 2(1.7%) and mixed genotype (5.1%) respectively, when compared to other studies in which genotype 4 cases were also reported. 16,17 In this study, 89.83% of naïve cases while only 10.2% had a previous history of HCV treatment with an interferon based regime, among which 3.38% showed treatment failure and 6.7% relapses.…”
Section: Discussioncontrasting
confidence: 46%
“…Our findings correlate with the recent phase 3 trials done, which showed that DAA therapy achieved Daclatasvir-Sofosbuvir Combination Therapy Pak Armed Forces Med J 2023; 73(5): 1520 high SVR rates (more than 90% for genotype-1, 80-90% for genotype-2, 60-70% for genotype-3) for compensated cirrhotic patients, with high tolerance & relatively low rates of adverse effects. 15 In our study, genotype 3(81.3%) was more common, followed by genotype 1(11.8%), with few cases of 2(1.7%) and mixed genotype (5.1%) respectively, when compared to other studies in which genotype 4 cases were also reported. 16,17 In this study, 89.83% of naïve cases while only 10.2% had a previous history of HCV treatment with an interferon based regime, among which 3.38% showed treatment failure and 6.7% relapses.…”
Section: Discussioncontrasting
confidence: 46%
“…The morbidity of virus-related hepatocellular carcinoma (HCC) has been decreasing worldwide because of vaccination, antiviral therapy, and screening of transfused blood. [1][2][3] Nevertheless, HCC is still one of the main leading causes of cancer-related death worldwide. 4 One reason may be that the morbidity of non-B, non-C (NBNC) HCC, which is negative for the hepatitis-B surface antigen (HBsAg) and hepatitis-C (HCV) antibody, has been increasing continuously.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis C virus (HCV) is a single-stranded RNA virus that targets hepatocytes and a member of the Flaviviridae family [1]. HCV represents one of the most common causes of chronic liver disease and, therefore, represents a major global public health problem [2]. HCV causes debilitating liver disease, which may progress to cirrhosis and cancer, and claims 500,000 lives annually worldwide [3].…”
Section: Introductionmentioning
confidence: 99%
“…Various authors consider the sudden decrease in viral load achieved with DAAs as a cause of distortion in the immune system [8]. As previously mentioned, a multistep process of HCV-induced hepatocarcinogenesis consists of a combination of pathway alterations caused either directly by viral factors or by the effect of immune mediators as a consequence of chronic inflammation, as shown in Figure 1 [2].…”
Section: Introductionmentioning
confidence: 99%